Tratados internacionais de direitos humanos e conflitos com o vértice do ordenamento jurídico nacional: atualização do princípio pro homine na ponderação de colisões normativas que envolvam direitos humanos - Sousa, Ileide Sampaio de (2013)
The use of the principle in international Pro Homine weighting rules involving the contents of human rights as an instrument of abandoning formalistic criteria for setting hierarchical rules - having understood the dynamic character of the legal system, and not just static staggered. The perpecpção that humanity historically and psychologically, is animated by universal ideals with intent, and, although the same can not be defended in a uniform way, are always being recreated. The analysis of the case law of the Supreme Court from the classical analysis of the resolution of normative conflicts between International Treaties on Human Rights and National Constitution upon theses Monist and Dualist, and the status conferred to these international treaties, especially after the Constitutional Amendment . 45 of 30 December 2004, which led to the innovative thesis status supralegalidade and discussion on the materials and formal constitutionalization of International Treaties on Human Rights. The contribution of the New Grammar and Hermeneutics Dieito the Constitution and with the acceptance of normative principles, revolutionizing the hermetic classic classical theory of legal origin kelseniana. The displacement of the normative focus dedutico legalistic, with the call neoconstitutionalism and hard cases, where the norm in theory contribute little to resolve the collision of norms of open texture as are the standards of human rights and fundamental. The emergence of the concept of Weighting Principles and collision with the link of a methodical differentiated emphasizes that the court decision and not a normative position of a legal text, and the advancement of the standard more favorable to the victim use originally in current international treaties on Human Rights , which led to the abandonment of international law conflicting with national and made room for the use of Pro Homine Principle. The perception that the Principle of Proportionality can be driven by a fourth dimension or subprinciple, besides those already existing: appropriateness, necessity and proportionality stricto sensu. May be, in case of collisions involving normative standards of human rights, waived the formal analysis of hierarchical criterion of source, using the Principle Pro Homine to determine if it is applied to the standard that best protects the human being.